The effects of resistance training on fasting blood glucose and power strength on overweight men / Muhammad Haikal Zawawi … [et al.] - Zawawi, Muhammad Haikal; Nural Azhan, Mohd Azim; Abu Bakar, Al-Hafiz; Shafee, Siti Syahirah Aqilah; Ismail, Ahmad Dzulkarnain; Gray, Stuart (Universiti Teknologi MARA, 2023)
Resistance training has numerous advantages, including increased in muscle strength, endurance, and overall health. The goal of this study was to determine and compare the effect of 6 weeks of voluntary to failure resistance training on fasting blood glucose and power strength in overweight men who took part in one session per week (1TPW) or three sessions per week (3TPW) sessions per week. Fourteen overweight men age: 29±9 years; weight: 80.7±5.9 kg; height: 169.8±5.6 cm; BMI: 27.9±1.2 kg/m2 were selected for this study. Each training session comprising nine exercises performed at 80 percent of one repetition maximum (1RM) to volitional failure. Fasting blood glucose and power strength were measured every week, beginning with the baseline. Paired sample t-test was used to compare the baseline and post-intervention outcome. The result showed a significant difference (p<0.05) in fasting blood glucose and power strength for both groups. However, the 3TPW group had a greater improvement in terms of percentage in reducing fasting blood glucose and increasing power strength on overweight men. Group 1TPW fasting blood glucose decreased by 18% while group 3TPW decreased by 55.4%. Meanwhile, group 1TPW power strength increased by 14.2% compared to group 3TPW increased by 41%. There were significant differences between 1TPW and 3TPW resistance training on fasting blood glucose and power strength. In conclusion, training 1 time per week or 3 times per week are beneficial in reducing fasting blood glucose and increasing power strength. However, training three sessions per week resulted in greater increases in muscle strength and blood glucose compared to one session per week.